Web based system for tanah Perkuburan Islam Taman Uda, Alor Setar, Kedah / Nurul Fatin Nurjeha Hussin - Hussin, Nurul Fatin Nurjeha (2019)
This study is designed for the development of Web Based System for Muslim Cemetery at Taman Uda, Alor Star, Kedah. Until now, records of funeral information are traditionally done by handwriting on a hard copy of a log book. The usage easy and the modification can be made directly. However, this is not parallel with the ever-expanding technological advancement as these advances can help many parties in facilitating various affairs in the future. Therefore, the aim of this research is to develop the cemetery information system of Tanah Perkuburan Islam Taman Uda, Alor Setar, Kedah using GIS approach with the three objectives which is to spatially map the existing cemetery, to create a database of cemetery and to develop a web- based system for Tanah Perkuburan Islam Taman Uda. The software used for this research are ArcGIS, Microsoft Excel and also Adobe Dreamweaver. GIS can present an ideal framework in terms of storing, compiling, and controlling each record spatially and their attributes. New functionality can also be realized by creating a navigational facility to ease every visitor to this cemetery. All of these can be demonstrated through the use of a web-based technology system capable of integrating with Google Maps to display the actual location of the funeral so grave map can be plotted accurately with perfect detail of information. The last product is a web- based system of the cemetery that will greatly help visitors to do research about the information before visiting the cemetery. This grave plot information can also assist the management in terms of the accuracy and managing of the data information recorded for reference purposes as well as future use.